Mantle cell lymphoma presenting with lethal atraumatic splenic rupture - Frederick Eyerer; Juli-Anne Gardner; Katherine A. Devitt (University of São Paulo, 2021)
Mantle cell lymphoma is characterized by t(11;14) with CCND1-IGH fusion and manifests with a spectrum of disease ranging from relatively indolent to aggressive. Here, we present a case of pleomorphic mantle cell lymphoma with three fusion signals that presented with lethal atraumatic splenic rupture. We discuss on the implications of variant CCND1 signal patterns as well as the epidemiology and pathophysiology of atraumatic splenic rupture.